2020
DOI: 10.1007/s00345-020-03178-z
|View full text |Cite
|
Sign up to set email alerts
|

What is the exact definition of stone dust? An in vitro evaluation

Abstract: Purpose To propose a size-related definition of stone dust produced by lithotripsy of urinary stones. Methods Stone dust was defined as particles small enough to adhere to the following criteria: (1) spontaneous floating under 40 cm H 2 O irrigation pressure; (2) mean sedimentation time of > 2 s through 10 cm saline solution; (3) fully suitable for aspiration through a 3.6 F working channel. Irrigation, sedimentation, and aspiration tests were set up to evaluate each criterion. Primary outcome was particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…To date, there is no consensus regarding the exact definition of dust; nonetheless, a size limit of ≤250 μm seems to properly adhere to an adequate definition of stone dust capable of being aspirated through the working channel [ 62 ]. Laboratory studies have suggested that the TFL produces smaller fragments than the Ho: YAG laser does in dusting mode, regardless of the stone type or laser settings [ 50 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no consensus regarding the exact definition of dust; nonetheless, a size limit of ≤250 μm seems to properly adhere to an adequate definition of stone dust capable of being aspirated through the working channel [ 62 ]. Laboratory studies have suggested that the TFL produces smaller fragments than the Ho: YAG laser does in dusting mode, regardless of the stone type or laser settings [ 50 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by noncontact lithotripsy (popcorning), until fine dust, small enough to pass spontaneously, was formed. [ 12 ] Thus, popcorning is common in both modes, at the end, to obtain fine dust. No stone retrieval was done after fragmentation mode.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] The ablation rates are two-fold higher than Ho YAG laser from the reports of in vitro studies[ 8 9 10 ] and ablation volume is 2.2, 2.0, and 1.6 times higher than short pulse, long pulse, and Moses modes of Ho YAG laser. [ 11 ] The preclinical studies propose that TFL enables achieve faster and finer “Dust,”[ 12 ] as very low pulse energy and very high frequency is possible. [ 6 ] Claimed to have so many advantages, this study assessed the application of TFL in a clinical scenario.…”
Section: Introductionmentioning
confidence: 99%
“…"Dust" has been recently defined as fragments floating under irrigation [29]. Whereas Keller et al demonstrated in vitro that fragments smaller than 250 µm, except for struvite (125 µm), met this definition; the SFR level is still under discussion [30,31]. Consequently, we left the SFR assessment to the surgeon's preference.…”
Section: Clinical Evaluationmentioning
confidence: 99%